Temporal variation of bacterial respiration and growth efficiency in tropical coastal waters - Lee, C.W.; Bong, C.W.; Hii, Y.S. (American Society for Microbiology, 2009)
We investigated the temporal variation of bacterial production, respiration, and growth efficiency in the tropical coastal waters of Peninsular Malaysia. We selected five stations including two estuaries and three coastal water stations. The temperature was relatively stable (averaging around 29.5 degrees C), whereas salinity was more variable in the estuaries. We also measured dissolved organic carbon and nitrogen (DOC and DON, respectively) concentrations. DOC generally ranged from 100 to 900 microM, whereas DON ranged from 0 to 32 microM. Bacterial respiration ranged from 0.5 to 3.2 microM O2 h(-1), whereas bacterial production ranged from 0.05 to 0.51 microM C h(-1). Bacterial growth efficiency was calculated as bacterial production/(bacterial production + respiration), and ranged from 0.02 to 0.40. Multiple correlation analyses revealed that bacterial production was dependent upon primary production (r2 = 0.169, df = 31, and P < 0.02) whereas bacterial respiration was dependent upon both substrate quality (i.e., DOC/DON ratio) (r2 = 0.137, df = 32, and P = 0.03) and temperature (r2 = 0.113, df = 36, and P = 0.04). Substrate quality was the most important factor (r2 = 0.119, df = 33, and P = 0.04) for the regulation of bacterial growth efficiency. Using bacterial growth efficiency values, the average bacterial carbon demand calculated was from 5.30 to 11.28 microM C h(-1). When the bacterial carbon demand was compared with primary productivity, we found that net heterotrophy was established at only two stations. The ratio of bacterial carbon demand to net primary production correlated significantly with bacterial growth efficiency (r2 = 0.341, df = 35, and P < 0.001). From nonlinear regression analysis, we found that net heterotrophy was established when bacterial growth efficiency was <0.08. Our study showed the extent of net heterotrophy in these waters and illustrated the importance of heterotrophic microbial processes in coastal aquatic food webs.